Chromosome aberrations in lymphocyte cultures from paracoccidioidomycosis patients - Freire-Maia, D. V. [UNESP]; Garcia, M. G. [UNESP]; Mendes, R. P. [UNESP]; Marques, S. A. [UNESP]; Curi, P. R. [UNESP]; Souza, L. R. [UNESP] (Blackwell Science, 1994)
Blood cell lymphocyte chromosomes from untreated (UT) and clinically-cured (CC) patients with paracoccidioidomycosis and from healthy (control) people (CO) were studied. The frequency of aneuploid cells in the UT patients was higher than in the CC and CO individuals. The frequency of metaphase cells with premature centromere division was significantly higher in the UT than in the CC and CO group. No structural aberration and no statistically significant difference in the frequency of polyploidy was observed in the three groups studied. Our findings are indicative of an aneugenic (aneuploidy-inducing) action of infection by Paracoccidioides brasiliensis.
Keywords: Adult; Aneuploidy; Chromosome aberration; Controlled study; Human; Human cell; Lymphocyte culture; Major clinical study; Male; Metaphase; Mycosis; Polyploidy; South american blastomycosis; Adult; Chromosome Aberrations; Female; Human; Lymphocytes; Male; Metaphase; Middle Age; Paracoccidioidomycosis; Ploidies; Support, Non-U.S. Gov't